Deficit Irrigation Strategies for Subsurface Drip-Irrigated Alfalfa - Rocio Reyes Esteves; Keith Harmoney; Freddie R. Lamm (Kansas Agricultural Experiment Station Research Reports, 2024)
This subsurface drip-irrigated study was conducted from 2020 to 2023 at the Kansas State University Northwest Research-Extension Center near Colby, KS, to evaluate five deficit irrigation strategies for alfalfa. The alfalfa crop was irrigated for the full growing season and harvested only from 2020 to 2022. Irrigation strategies focused on optimizing alfalfa production with a highly efficient Subsurface Drip Irrigation (SDI) system. Treatments were irrigated in a similar fashion (100% of Evapotranspiration (ET) minus Rain) through the first cutting. Following the first harvest, treatments were 1) Irrigate to replace 85% ET minus Rain; 2) Irrigate to replace 50% ET minus Rain between Cutting 2 and 3, then 85% ET - Rain; 3) Irrigate to replace 50% ET minus Rain between harvest 2 and 4, then 85% ET - Rain; 4) Irrigate to replace 70% ET minus Rain between harvest 2 and 4, then 85% ET - Rain; and 5) Irrigate to replace 25% ET minus Rain between harvest 2 and 3, then 85% ET - Rain. Average alfalfa forage dry matter yields varied across treatments (9.14 vs. 9.60 ton/a), while irrigation requirements varied by 20% (17.38 vs. 22.62 inches). Overall, the best treatments appeared to be treatments 2, 3, and 5, obtaining both good, reasonable yields and greater water productivity.
Keywords: alfalfa; subsurface drip irrigation; deficit irrigation; yield; water productivity